La femme fugitive dans ‘’A une passante’’ de Charles Baudelaire (Journal of the College of Languages (JCL), 2014)
The main subject of this poem is a chance meeting between Baudelaire and unknown beautiful lady. Her presence represents the far-fetched, magnificent beauty. This beauty forms an aspect of idealism that takes its real existence and disappears immediately. This emotional poem deals with the continuous despair that dates back to the Romantic age where it was a key topic; the passing woman embodies destiny. All this comes from constant experience and mad love through the poet’s view to a woman paving the way toward the unknown. Baudelaire, however, noticed this unknown through a passer-by that reflected the real and magical image of this unknown. In addition, the poem’s content describing this emotional meeting was fuzzy and mysterious: The presence of the passing woman was disappointing for the poet because it was incidental, surprising and destined to fail before it happens. This woman stood for the attractive and destructive image at the same time, so it expressed a huge contradiction. Thus, Baudelaire invested his failure to create a beautiful poetic painting that expresses the solitude of human condition.